Corporate strategy for Metropolitan Bank and Trust Company - Ching, Christine (Animo Repository, 1999)
The Banking industry in the Philippines is highly competitive. There are more than seventeen thousand banks and branches competing with one another to get a share of the market. With similar products and services being offered, banks have to find a unique selling point to lure clients to bank with them. Metrobank is one of the major players in the industry. It has sustained its number one position for four years. However, with the banking liberalization, the increasing entrant of foreign banks, with the Asian currency crisis in 1997, Metrobank faces a great challenge. To sustain its position and achieve growth, strategic programs need to be implemented. An analysis of the bank using Michael Porters five-forces model, the SWOT analysis has been undertaken to determine what advantage it has and what needs to be acquired to get ahead in the industry. Metrobank has to consider that the threat of rivalry among competitors is very high. Threat of new entrants is moderate, considering the huge capital investment needed to put up a bank. The bargaining power of buyers is high, especially in Metro Manila. Nevertheless, Metrobank has the financial, technical and human resources to take advantage of the opportunities and face the challenges ahead of her. With its vision of being the biggest and the best, its mission of being a premier universal bank of international standing, its company culture of hardwork, its competent professional staff, its extensive branch network, its wide array of products and services, Metrobank has been able to provide efficient, personalized service to diversified clients. At present, Metrobank has embarked on changes. It has installed a new computer system, called Mosaic that is supposed to hasten transactions. Reengineering will enable front-liners to concentrate on servicing clients. Furthermore, it continuously provides training and seminars to its employees for work and personal enhancements. Yet, with these changes, the need to differentiate its products from other banks is necessary. The needs of clients are becoming more sophisticated. Telephone banking, an offshoot of virtual banking is in. There is the trend of virtual banking, where people can transact their banking needs at home or in the office through their personal computers. Metrobank faces a great challenge. It has to come up with strategies to continue its growth. Implementation of strategies will have to be in harmony with its organizational structure and company policies.